Evaluation of Cryptography Usage in Android Applications - Chatzikonstantinou, Alexia; Ntantogian, Christoforos; Karopoulos, Georgios; Xenakis, Christos (EAI Endorsed Transactions on Security and Safety, 2016)
Mobile application developers are using cryptography in their products to protect sensitive data like passwords, short messages, documents etc. In this paper, we study whether cryptography and related techniques are employed in a proper way, in order to protect these private data. To this end, we downloaded 49 Android applications from the Google Play marketplace and performed static and dynamic analysis in an attempt to detect possible cryptographic misuses. The results showed that 87.8% of the applications present some kind of misuse, while for the rest of them no cryptography usage was detected during the analysis. Finally, we suggest countermeasures, mainly intended for developers, to alleviate the issues identified by the analysis.